Beyond environmental Kuznets curve and policy implications to promote sustainable development in Mediterranean. (November 2021) - Gyamfi, Bright Akwasi; Adebayo, Tomiwa Sunday; Bekun, Festus Victor; Agyekum, Ephraim Bonah; Kumar, Nallapaneni Manoj; Alhelou, Hassan Haes; Al-Hinai, Amer
Abstract: In acknowledgment of the devastating consequences of environmental deterioration, the Mediterranean members are committed to adopt the 2015 treaty action plans of the Paris Climate Agreement (COP21) as carbon dioxide emission (CO2 ) are on the rise in the Mediterranean region, which seems to be a serious challenge to our world's environment. To this end, our study examined the impact of Foreign Direct Investment (FDI) on environmental degradation for the Mediterranean members for the period between 1995 to 2016. However, variables such as, financial development, economic growth, renewable energy and fossil fuel were further examined by the use cross-sectional-Panel pooled Auto Regressive Distributed Lag methodology, Augmented Mean Group (AMG) and Dumitrescu and Hurlin panel causality test was used for causality analysis. The co-integration results from Westerlund (2007) shows a long-run equilibrium relationship between highlighted variables. The empirical result revealed a negative relation between FDI and CO2 indicating pollutant Hallo Hypothesis (PHH). Moreover, income and its square show an inverted U-Shaped curve indicating environmental Kuznets curve (EKC) hypothesis. Both financial development and renewable energy indicated an adverse association with CO2 emission whereas fossil fuel had a positive relationship with emissions. However, there was a feedback causality among income and carbon emission as well as financial development and carbon emission. Furthermore, we observe that FDI and carbon emission, renewable energy and carbon emission, as well as fossil fuel and carbon emission were found to have one-way causal relationship. Overall, the study suggests some policy prescriptions including the implementation of conservation initiatives and the establishment of clean energy regulation and strategies for the investigated bloc.